CONCOMITANT OF ANAPLASMOSIS WITH ACID-BASE BALANCE ,BLOOD GAS ANALYSIS , ACUTE PHASE RESPONSE AND HEMOGRAM IN CATTLE - Kamal.M. Alsaad Hussam.MS. Alimam (Basrah Journal of Veterinary Research)
The objective of the present work was to evaluate Hemogram, acid-base balance, blood gas analysis and acute phase response in cattle infected with anaplasmosis in Mosul,Iraq.The study were conducted on (167), local cattle breed 2-5 years old of both sexes. Eighty local cattle breed out of (167) were clinically infected with Aanaplasam marginale since the causative Rickettsia diagnosed by Giemsa stained blood smears and confirmed by indirect Elisa test. (20) clinically normal cattle were served as controls. Results indicated statistically significant decrease (P